The effect of resistance exercise combined with L-arginine supplementation on the expression of VEGF and TNF-α genes in the soleus muscle of aged male rats - Mahnoosh Shahbani Nazari; Elham Farhadfar (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: One of the significant changes during aging is the loss and degradation of muscle mass, increased inflammation, and a notable reduction in vascular factors. The aim of this study was to determine the effect of resistance exercise combined with L-arginine supplementation on the expression of VEGF and TNF-α genes in the soleus muscle of aged male rats. Methods: In this experimental study, 32 male Wistar rats, with an average age of 24 months, were divided into four groups: control, supplementation (L-arginine), resistance exercise, and combined (resistance exercise + L-arginine). The resistance exercise program included 8 weeks of ladder training at moderate intensity (70% of maximal voluntary contraction), five days per week. In the supplementation and combined groups, L-arginine was administered via gavage at a dose of 600 mg per kg of body weight, five days a week for 8 weeks. Gene expression of VEGF and TNF-α was measured using Real-Time PCR. Results: The expression of the TNF-α gene was significantly reduced in the resistance exercise and combined groups compared to the control and supplementation groups (P=0.001). Similarly, VEGF gene expression was significantly higher in the resistance exercise and combined groups compared to the control and supplementation groups (P=0.001). No significant difference was observed between the control and supplementation groups (P=0.266). Conclusion: The results of this study indicate that both resistance exercise alone and in combination with L-arginine supplementation can enhance VEGF expression and reduce TNF-α levels, promoting angiogenesis, reducing inflammation, and creating an anabolic environment. These factors contribute to improving muscle condition and mitigating the effects of aging. The findings suggest that the combination of resistance exercise and L-arginine supplementation may play an important role in preserving muscle mass during aging.